2015
DOI: 10.5539/jas.v7n10p17
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficiency Foliar Nitrogen and Pyraclostrobin Applications for High Yielding Corn

Abstract: Combining a foliar fertilizer and fungicide in a single application could complement soil-applied nitrogen (N) and reduce application costs. Limited research has evaluated such combinations for high-yield corn (Zea mays L.) production systems. This research evaluated the effect of mixing order of enhanced-efficiency foliar N (30-0-0-0, Nitamin) rates (0, 9, and 28 L ha -1 ) with pyraclostrobin under different crop-yield environments (soil applied N at 84, 169, and 337 kg ha -1 ) on crop injury, disease severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Pyrazoxystrobin is an important class of respiratory inhibitors, mainly acting on cytochrome bc1Q0 ubiquinone oxidase. It is widely used in the prevention and cure of maize leaf spot diseases [42]. In order to avoid the rapid development of resistance to pyrazoxystrobin and prolong its lifespan, it is necessary to search for an exogenous substance that can enhance its inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrazoxystrobin is an important class of respiratory inhibitors, mainly acting on cytochrome bc1Q0 ubiquinone oxidase. It is widely used in the prevention and cure of maize leaf spot diseases [42]. In order to avoid the rapid development of resistance to pyrazoxystrobin and prolong its lifespan, it is necessary to search for an exogenous substance that can enhance its inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially, Consist Max ® is a fungicide with tebuconazole (triazole) and trifloxystrobin as active ingredients. This compound belongs to the group of strobilurins, which decrease the severity of P. sorghi and significantly increase the maize grain yield (Carmona et al, 2009;Nelson et al, 2015). According to Lazo and Ascencio (2014), in addition to a fungicide action, the strobilurins have a positive influence on the metabolic and physiologic processes, by altering the phytohormone levels, delaying senescence processes and increasing grain yield.…”
Section: Healthy and Rotten Earsmentioning
confidence: 99%
“…However, some corn growers are including foliar N as an additive to foliar fungicide applications at pollination to optimize yield. Nelson et al (2015) reported yield increases associated with pyraclostrobin [methyl N ‐(2‐ [(1‐[4‐chlorophenyl]pyrazol‐3‐yl)oxymethyl]phenyl)‐ N ‐methoxycarbamate] combined with a foliar N application at anthesis in high‐yielding environments. However, Shetley et al (2015) found no evidence of synergistic responses in an evaluation of common foliar fertilizers applied with and without pyraclostrobin.…”
Section: Intensive Agronomic Management Practices Impact Grain Yieldmentioning
confidence: 99%
“…Growers who have achieved record grain yields in the National Corn Yield Contest (National Corn Growers’ Association, 2019) promote these practices. Several university studies also indicate that these methods may help corn growers increase yields (Ruffo et al, 2015; Nelson and Meinhardt, 2011; Nelson et al, 2015).…”
Section: Intensive Agronomic Management Practices Impact Grain Yieldmentioning
confidence: 99%